Tradisi Adat Pernikahan Mulia Pada Masyarakat Desa Rubit Ditinjau Dari Prespektif Agama Katolik - Saverinus Heryanto; Gisela Nuwa; H. Rodja Abdul Natsir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to find out how the implementation of the traditional traditions of noble marriages in Rubit Village and the perspective of the Catholic religion on noble marriages. This research method was carried out with a qualitative descriptive approach. The data sources used are primary data sources and secondary data sources. The informants involved in this research were the traditional leaders of Rubit Village, community leaders and the parish priest of the Holy Cross of Koangrotat. Data collection techniques used are observation techniques, interviews and documentation. Data analysis techniques include data collection, data reduction, drawing conclusions and verification. The research results obtained are that noble marriage is the most respected marriage because it contains the most noble and sacred values ​​to maintain human dignity. So that noble marriage is processed in an open, orderly and respectable manner and is planned based on the perspective of custom and religion. The perspective of the Catholic religion on noble marriages is that marriages are considered sacred because in noble marriages the rite of opening the veil is performed which is a symbol that the couple has not lived together.